Cultivating curiosity: integrating hybrid teaching in courses in human behavior in the social environment - Rodriguez-Keyes, Elizabeth; Schneider, Dana A (Journal of Teaching in Social Work, 2013)
This study illustrates an experience of implementing a hybrid model for teaching human behavior in the social environment in an urban university setting. Developing a hybrid model in a BSW program arose out of a desire to reach students in a different way. Designed to promote curiosity and active learning, this particular hybrid model has students engage in weekly online activities between their weekly on-ground classes. This article reviews key pedagogical concerns and presents preliminary findings, including student feedback, instructor observations, and strategies for faculty interested in developing such courses. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: dept.swk; education; hybrid; online; peer-reviewed; social work; student perceptions; technology